Role of agricultural commercialization in the agricultural transformation of Ethiopia: Trends, drivers, and impact on well-being - Minot, Nicholas; Warner, James; Aredo, Samson Dejene; Zewdie, Tadiwos (International Food Policy Research Institute, 2022)
Agricultural transformation refers to a series of changes in agriculture that both reflect and drive rising income and economic development more broadly. While the macroeconomic patterns of agricultural transformation are relatively well documented, less is known about how it is manifested at the household level. Ethiopia makes an excellent case study as it has had one of the fastest growing economies in the world. This paper focuses on one aspect of this process: agricultural commercialization, that is, the process through which an increasing share of agricultural output is sold on the market rather than being consumed at home. The analysis uses three nationally representative rural household surveys carried out in 2012, 2016, and 2019, including a panel of 1,900 households. The results show that the share of marketed agricultural output has increased significantly over the seven-year period. Somewhat surprisingly, this increase is not due to a shift in crop mix toward more commercial crops but rather an increase in the degree of commercialization of each crop. Using a correlated random effects model, we find marketed share to be significantly related to age of the head of household, farm size, wealth, distance to road, rainfall, rainfall variability, and region. Although endogeneity is a challenge, descriptive statistics and regression analysis further suggest that agricultural commercialization contributes to higher income, largely because commercial crops generate higher returns per hectare than staple grains. The results indicate that there is no clear line between “subsistence” and “commercial” farms. A large majority of farms have some crop sales, while virtually none of them sell all their output. Similarly, the contrast between subsistence crops and cash crops can be misleading. For example, the value of staple cereal sales in Ethiopia is almost three times greater than that of coffee, the main cash crop. We draw lessons from the results for the design of programs to raise rural incomes by facilitating market-oriented agricultural production.